A feminist hacklab's resilience towards anti-democratic forces. (April 2022) - Wuschitz, Stefanie
Makerspaces and hacklabs are believed to encourage a positive attitude towards gaining computer skills. Within these communities for peer production, citizens can apply cutting-edge technologies in DIY projects. In recent decades, mushrooming makerspaces and hacklabs were embraced by the tech industry and governments alike. Feminist makerspaces and hacklabs, however, as they are centred around a queer feminist agenda, have raised eyebrows. In order to foster diversity in tech development, they create safer spaces for self-expression. Here, feminist lay(wo)men* (To emphasise that the category 'Woman' is constructed and that more people than only those who identify as women are being included, one uses the sign * after the term 'women' ), makers, designers, artists and tinkerers experiment with open-source hardware and software. Art and design projects emerging from feminist hacklabs focus on issues of representation and democratic participation in digital media, as well as on ways of reclaiming one's own body. This article tries to unpack how, after an exhibition on sexual health norms, a feminist hacklab was attacked by local right-wing and conservative politicians. The attack resulted in the defunding of the feminist hacklab. But it also started a transformation process within the collective, as members became aware of critical interferences of diffracting marginalisations. The crisis triggered a discussion on how each member was threatened to very different degrees; for example, there was more at stake for members depending on their legal status in the country. The right-wing and conservative campaign against the feminist hacklab damaged the initiative, but at the same time it pushed the collective to generate increased vehemence and resilience.